Australia, the European Union and the New Trade Agenda - Elijah, Annmarie; Kenyon, Don; Hussey, Karen; van der Eng, Pierre (ANU Press, 2017)
"Australia (together with New Zealand) is one of the few Organisation for Economic Co-operation and Development (OECD) countries with which the EU does not have a comprehensive trade agreement. Australia and the EU are entering a new phase in the bilateral relationship, and the push towards a potential trade agreement has been steadily gaining momentum. This collection brings together diverse and deeply practical contributions to the forthcoming policy debate on the Australia-EU Free Trade Agreement (FTA), highlighting potential points of difficulty and possible gains from the agreement. This book makes two further contributions: it adds to the body of work reappraising the contemporary Australia-EU relationship; and provides a snapshot of current issues in trade policy-the 'new trade agenda'-which is more complex and politically visible than ever. The issues confronting Australia and the EU in forthcoming negotiations are those confronting policy makers around the globe. They are testing public tolerance of decisions once viewed as dull and technocratic, and are redefining the academic treatment of trade policy. '... this book is especially important because it is talking about a very different type of trade agreement than the ones Australia has concluded recently with our major trading partners in East Asia. An agreement with the EU inevitably will focus on issues like services, investment, government procurement, and competition policy. These are major issues in their own right, are key parts of the new trade agenda, and are critical to Australia's successful transition to a prosperous post-mining boom economy. In the absence of generalisable unilateral economic reform in this country, trade policy hopefully will provide an external source of pressure for reform. If this book adds to that pressure while also suggesting some of the tools needed for reform, it will have made a major contribution.' Dr Mike Adams, Partner, Trading Nation Consulting"